2022
DOI: 10.1039/d2qi00641c
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic lanthanide exchange between quadruple-stranded cages: the effect of ionic radius differences on kinetics and thermodynamics

Abstract: Seven different [Ln2L4]2− (Ln = La, Nd, Eu, Tb, Er, Tm and Lu) lanthanide-based quadruple-stranded helicates are here reported and transmetalation among pre-assembled cages was studied. Combining two homonuclear helicates...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Deprotonation of the ligand with tetraethylammonium hydroxide (TEAOH) and subsequent addition of a Eu 3+ inorganic salt leads to the selfassembly of quadruple-stranded cages. We already reported elsewhere 24,25 25 one of the two tetraethylammonium cations is hosted by the quadruple stranded cage. In such quadruple-stranded Ln 3+ cages, ligands scaffold and guest molecule can influence the formation of helicates or mesocates.…”
Section: Luminophores Synthesismentioning
confidence: 92%
See 2 more Smart Citations
“…Deprotonation of the ligand with tetraethylammonium hydroxide (TEAOH) and subsequent addition of a Eu 3+ inorganic salt leads to the selfassembly of quadruple-stranded cages. We already reported elsewhere 24,25 25 one of the two tetraethylammonium cations is hosted by the quadruple stranded cage. In such quadruple-stranded Ln 3+ cages, ligands scaffold and guest molecule can influence the formation of helicates or mesocates.…”
Section: Luminophores Synthesismentioning
confidence: 92%
“…Ligands L B , L M and L A (Figure 1c) were prepared as previously reported. 24,25 The ligand L F (Figure 1c) is a modified version of L A bearing an additional -CF 2 -unit in the fluorinated terminal chains, to increase the cage solubility. This new ligand was prepared by a two steps procedure (Cu(I) catalysed N-C coupling reaction followed by a Claisen condensation) and fully characterized by NMR (Figure 2a), single crystal XRD (Figure S1, Table S1) and electrospray mass spectrometry (ESI-MS, Figure S3).…”
Section: Luminophores Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…However, Dolphin [21] reported that the same ligand and metal can lead to the formation of both isomers, while Raymond [22] highlighted how the host-guest interaction (even with the solvent) can shift the equilibrium toward the otherwise less stable species. In this context, recently we reported a series of lanthanide [Ln 2 L 4 ] 2− quadruplestranded helicates that show interesting supramolecular properties such as ion exchange to produce heterometallic systems [23] and adaptive helicity reorganization due to a guestto-host chirality transfer [24]. We also reported a DFT study for the helicity inversion and helicate-mesocate interconversion based on a Bailar twist, which demonstrated that the ligand scaffold nature (flexibility versus rigidity) plays a crucial role on the activation energy of the intramolecular helicate twisting mechanism [24].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the computational literature on lanthanide-based helicates (triple-and quadruple-stranded) is quite poor. Recent studies reported Perdew-Burke-Ernzerhof (PBE) in vacuum calculations for empty quadruple-stranded helicates, with Ln(III) ions and aromatic β-diketones [30], and also, in our preview studies, the same functional with the inclusion of solvent and dispersion correction was used to reproduce the geometrical structure [23] and the isomer stability [24] of the lanthanide organic cages. In addition, molecular mechanic calculations (Sparkle/RM1 model) on quadruple-stranded dinuclear Eu(III) helicate with bis-β-diketone ligand were considered [31,32].…”
Section: Introductionmentioning
confidence: 99%